The Influence of Consumer Dissatisfaction, Product Quality, and Competitor Advertisement toward Brand Switching - Ronaldo Diego Irviandra; Okki Trinanda (Universitas Negeri Padang, 2020)
The purpose of this research were to analyze: (1) The effect of Customer Dissatisfaction on Brand Switching for IPHONE users (2) The effect of Product Quality on Brand Switching for IPHONE users (3) The effect of Competitor Advertisement on Brand Switching for IPHONE users. The type of this research was causative research. The population on this research was college student who previously used IPHONE users and have switched to another brands. The total sample of this research was 150 person which was taken by using purposive sampling due to unknown the number of population. The result of research shows that (1)Consumer Dissatisfaction has significant effect on Brand Switching IPHONE smartphones (2)Product Quality has significant effect on Brand Switching IPHONE smartphones (3)Competitor Advertisement has significant effect on Brand Switching IPHONE smartphones. The conclusion is Consumer Dissatisfaction, Product Quality and Competitor Advertisement have significant effect on Brand Switching. Competitor Advertisement has higher influence on Brand Switching in this research. For the future research is better to explore more about variable that can inluence Brand Switching.